Bhutan Poverty Assessment 2014 - Bhutan National Statistics Bureau; World Bank (World Bank, Washington, DC, 2014)
This report identifies the key drivers of rapid poverty reduction in Bhutan over the recent years, explaining why some dzongkhags are stuck in poverty or reducing poverty is not significant while others prospered, and whether female headed households have a harder time reducing poverty. The exercise draws mainly on data from the two rounds of Bhutan Living Standards Survey (2007 and 2012) supplemented with focus group discussions carried out for the report in select dzongkhags. Bhutan's poverty reduction has been rapid, broad-based, and inclusive. Between 2007 and 2012, the percentage of consumption poor halved to 12 percent. Bhutan has nearly ended extreme poverty within the living memory of a generation extreme poverty touched a low of two percent in 2012. Broader multidimensional poverty indices, that include education and health outcomes besides standards of living, also indicate a steep decline in the percentage of deprived population by two-thirds, from about 25 percent to 12.7 percent. Growth in Bhutan helped the previously landless to escape poverty. Education appears to be the most important route by far to escape poverty. This report is a complement to the earlier Poverty Analysis Report 2012 which was prepared with the World Bank's technical support.